Public Spending and Learning Outcomes of Basic Education at the District Level in Indonesia - Thia Jasmina (Institute for Economic and Social Research, 2016)
Since 2009, the Indonesian government has fully allocated 20 percent of its budget on education. Though the increase of financial resources has led to an improvement of the access to education, challenges on the quality of education persist. By employing a cross-districts analysis in Indonesia during 2010–2015, this study aims to analyze the impact of government spending on the adjusted-national examination scores at the junior secondary education. This study shows that the central and local government spending have no significant impact on the scores. Whereas, the central government spending on teachers, and the socioeconomic factors such as poverty and health are significant determinants.AbstrakSejak 2009, Pemerintah Indonesia telah dapat mengalokasikan 20 persen anggaran untuk pendidikan. Peningkatan anggaran di sektor pendidikan yang signifikan di satu sisi telah meningkatkan akses pendidikan, tetapi di sisi lain masih terdapat tantangan terhadap kualitas pendidikan. Studi ini bertujuan untuk menganalisa dampak belanja pemerintah terhadap nilai ujian nasional SMP dengan menggunakan analisa cross-section di kabupaten/kota Indonesia pada tahun 2010–2015. Studi ini menunjukkan bahwa belanja pemerintah pusat dan daerah tidak mempunyai dampak yang signifikan terhadap nilai ujian nasional SMP. Akan tetapi, transfer pemerintah pusat untuk guru serta kondisi sosial ekonomi seperti kemiskinan dan kesehatan merupakan faktor yang signifikan.Kata kunci: Pendidikan; Belanja Pemerintah; Hasil Pembelajaran; Kabupaten/Kota; IndonesiaJEL classifications: H75; I22